Emerging Research in Electronics, Computer Science and Technology Proceedings of International Conference, ICERECT 2018 - Sridhar, V.; Padma, M.C; Rao, K.A. Radhakrishna (Lecture Notes in Electrical Engineering, 2019)
This book presents the proceedings of the International Conference on Emerging Research in Electronics, Computer Science and Technology (ICERECT) organized by PES College of Engineering in Mandya. Featuring cutting-edge, peer-reviewed articles from the field of electronics, computer science and technology, it is a valuable resource for members of the scientific research community. .